Impact of Business Risk and Capital Structure on the Growth of the Sea Transportation Companies - Lesse, Johan; Arubusman, Dian Artanti; Agusinta, Lira; Octora, Theresye Yoanyta; Purba, Okin Ringan; Purwoko, Harry; Haris, Haris (Institut Transportasi dan Logistik Trisakti, 2024)
The research aims to know and analyze the impact of business risk and capital structure on the growth of sea transportation companies listed on the Indonesia Stock Exchange in 2016-2020. Some of the problems encountered in this study, among others, namely, high business risk can reduce company growth, high capital structure can reduce company growth and also high debt to shipping companies can lead to difficulties in determining the composition of capital structure. Path analysis is used to test the hypothesis proposed in this study by using the Partial Least Square application. The total sample of 45 consisted of nine companies with a five-year observation period taken by purposive sampling technique. The results showed: business risk has no impact on firm growth, capital structure has no direct impact on company growth, business risk has a positive and significant direct impact on capital structure, and business risk does not directly impact company growth through capital structure mediation. The study concludes that business risk positively impacts capital structure, so the declining capital structure decreases business risk.